2014
DOI: 10.1051/matecconf/20141101009
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Moroccan coal waste: valorization in the elaboration of the Portland clinker

Abstract: Abstract. Coal exploited in the mine of Jerada (northeast of Morocco) was accompanied by large quantities of waste. The purpose of this work is to characterize this waste with the aim of its use as a material for civil engineering. Mineral and chemical investigations on this waste in the raw state, and at different temperature of heat treatments, were carried out by various methods: X-ray fluorescence, X-ray diffraction, infrared spectroscopy. These analyzes showed that the studied waste, contain essentially a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
1
9
0
Order By: Relevance
“…It was concluded that mine tailings alone and mixed with fly ash mine wastes can be favourably used as road embankment materials cost-effectively and sustainably. Also, the coal mine waste rocks (CMWR) wastes were successfully interred for the production of eco-friendly fired bricks at a laboratory scale [10,11], in the production of cement [12,13] and asphalt concrete products [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that mine tailings alone and mixed with fly ash mine wastes can be favourably used as road embankment materials cost-effectively and sustainably. Also, the coal mine waste rocks (CMWR) wastes were successfully interred for the production of eco-friendly fired bricks at a laboratory scale [10,11], in the production of cement [12,13] and asphalt concrete products [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Due to limited resources and the environmental impacts caused by some materials, researchers began to explore strategies for new ecologically correct materials, considering the source of the raw material, its properties, and final disposal (Govindan et al 2016). Considering its composition, coal mining waste (CMW) has been researched as a raw material in the development of new materials, including ceramics and light aggregates, cement compounds, burned brick compounds, concrete, brick compounds, asphalt filler, dyes, and enamelling (Taha et al 2017;Taha et al 2018;Haibin and Zhenling 2010;Belkheiria et al 2015;Wang et al 2016;Jung et al 2005; Modarres and Rahmanzadeh 2014; Darmane et al 2009). Given the research carried out to understand in which materials the use of CMW is being used, no research mentions the use of hydrophobic polymer matrices in the formulation of composites materials with CMW.…”
Section: Introductionmentioning
confidence: 99%
“…Oil shale is one of humanity's most promising sources of energy and chemicals (4) and Morocco has one of the world's largest oil shale reserves (5). Moreover, the Jerada coal mine in the country's northeast generates large amounts of waste (6)(7)(8), with the recoverable total estimated at 134.482 (short) Gt.Valorising that waste would reduce stockpiling, solving urban planning problems and mitigating the environmental impact of pyrite oxidation in the waste (9).…”
Section: Introductionmentioning
confidence: 99%